Special Method of Formation of Social Competence of Adolescents with Intellectual Disorders - Utosov, Yan; Utosova, Olena (Pedagogical Discourse, 2020)
Social competences are functional tasks related to social activities or social behavior that a teenager can successfully solve. In the article some important components of social competence are given. The scientific article deals with the problem of formation of social competence of teenagers with mental retardation. The basic concept of research is defined. The author understands the social competence as the mastering of the corresponding competence, including teenager’s personal attitude to the subject of social activity or social behavior. The method assumes the formation of competencies that will allow within a sharp change of pedagogical conditions during the training period of the child at school, take into account the needs and capabilities of each student and guide the work on the specific competencies of each student, which is important on the next stage of training, by reorganization or the development. However social competences are the ability to build interpersonal relationships, have a joint activity, norms of behavior, communication in society, soft technologies, ability to work in team, under leadership, etc. The author scientifically substantiates the specifics of psychological and pedagogical influence on the social competence formation of teenagers with intellectual disorders. The article describes the main conditions and specifics of the special method for the formation of social competence of the teenagers. This is the formation of a strong and lasting active motive; the introduction of restrictive purposes; consistency and independence of action; consolidating the skills of actions moving into new conditions from lesson to extracurricular work, etc. For the successful integration of method in the system of education the author of the article has identified and developed the principles according to which this model will be possible to implement in practice. As a basis for the integration of case-method in the structure of secondary education, modern educational standards aimed at forming competencies are taken. The article contains a detailed description of the stages and application of the model on the formation of social competence of adolescents at school in curricular and extracurricular activities.